Proof of concept study of a novel bioadhesive clindamycin phosphate 2% vaginal gel to treat bacterial vaginosis - A. Dupre; H.H. Alur; D.R. Friend (Clinical and Experimental Obstetrics & Gynecology)
The objective of the study was to evaluate the efficacy and safety of a novel single 2% clindamycin phosphate vaginal gel for the treatment of bacterial vaginosis (BV). The vaginal gel, a thermosetting bioadhesive formulation containing 2% clindamycin phosphate, was studied in a single center, single arm, open-label study. Patients (n = 30) were screened for BV using the four Amsel criteria (visit 1). A subset of ten women were also assessed using Nugent scores. Eligible patients were consented and provided a single dose of 2.0% clindamycin phosphate gel in a prefilled vaginal applicator (5-gram total dose). Patients returned to the clinic 7 to 14 days (visit 2) after dosing and again between 21 and 30 days (visit 3). Two subjects were excluded from cure rate calculations. Of the evaluable 28 patients, 24 (86%) were successfully treated (clinical cure) with a single dose of 2% clindamycin gel at visit 2. Of the ten patients evaluated for Nugent scoring, seven subjects were evaluable for bacteriologic cure. After a single dose of 2% clindamycin gel, four of seven (57%), and four of seven (57%) had a bacteriologic and therapeutic response, respectively. Of the 24 women who completed visit 2 and were cured based on Amsel criteria, 23 (96%) remained cured at visit 3. Of the subset of ten patients evaluated using Nugent scoring (bacteriologic evaluation), seven of nine (78%) had a score of 3 or less at visit 3. In this group, six of nine women were considered therapeutically cured (67%). There were no reports of adverse reactions, including local reactions to the vaginal gel product over the course of the study. These data support the expanded clinical evaluation of 2% clindamycin gel.